Hypersexuality and headscarves race, sex, and citizenship in the new Germany - Partridge, Damani J. 1973- (Indiana Univ. Press, 2012)
"Damani J. Partridge explores citizenship and exclusion in Germany since the fall of the Berlin Wall. That event seemed to usher in a new era of universal freedom, but post-reunification transformations of German society have in fact produced noncitizens: non-white and "foreign" Germans who are simultaneously portrayed as part of the nation and excluded from full citizenship. Partridge considers the situation of Vietnamese guest workers "left behind" in the former East Germany; images of hypersexualized black bodies reproduced in popular culture and intimate relationships; and debates about the use of the headscarf by Muslim students and teachers. In these and other cases, which regularly provoke violence against those perceived to be different, he shows that German national and European projects are complicit in the production of distinctly European noncitizens"
Keywords: Unification of Germany / (1990); Since 1990; Geschichte 1990-2010; Citizenship / Germany; Foreign workers / Germany; Minorities / Germany; Political anthropology / Germany; Political anthropology; Post-communism / Germany; Race discrimination / Germany; Race discrimination; Sex discrimination / Germany; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Minority Studies; Citizenship; Foreign workers; Minorities; Political science; Post-communism; Race relations; Sex discrimination; Minderheit; Politische Wissenschaft; Political anthropology -- Germany; Race discrimination -- Germany; Sex discrimination -- Germany; Citizenship -- Germany; Minorities -- Germany; Foreign workers -- Germany; Post-communism -- Germany; Wiedervereinigung -- Deutschland; Diskriminierung; Deutschland